Increased number and frequency of group 3 innate lymphoid cells in nonlesional psoriatic skin. (1st March 2014) - Dyring‐Andersen, B.; Geisler, C.; Agerbeck, C.; Lauritsen, J.P.H.; Gúdjonsdottir, S.D.; Skov, L.; Bonefeld, C.M.
Summary: Background: Psoriasis is a common immune‐mediated inflammatory disease that affects the skin and joints. The interleukin (IL)‐23/IL‐17A axis and IL‐22 play key roles in the pathogenesis of psoriasis. IL‐23‐responsive innate lymphoid cells (ILCs) with a high capacity to produce IL‐17 and/or IL‐22 have recently been identified and associated with inflammatory bowel diseases. The occurrence and role of ILCs in human skin are poorly understood. Objectives: To describe the prevalence of the different ILC subpopulations in skin from healthy controls and patients with psoriasis or allergy to nickel. Methods: Skin biopsies were taken from healthy skin, nonlesional and lesional psoriatic skin, and nickel‐ and petrolatum‐exposed skin from patients with contact allergy to nickel, and lymphocytes were isolated. The cells were stained and characterized by flow cytometry. Cytokine and ligand mRNA expression were measured by quantitative polymerase chain reaction. Results: We found that members of the three groups of ILCs were present in human skin. Remarkably, the number and frequency of RORγt + CD56 + ILC3s, which are known to produce IL‐22, were elevated in both nonlesional and lesional skin from patients with psoriasis compared with healthy skin and skin from patients with contact allergy to nickel. Furthermore, skin ILCs expressed high levels of the natural killer receptor NKG2D. NKG2D binds to stress‐induced ligands, including major histocompatibility complex class I‐related chain A, which we found to be strongly upregulated in lesional skin from patients with psoriasis. Conclusion: These results show that ILCs are present in human skin and indicate that RORγt + CD56 + ILC3 may be involved in the pathogenesis of psoriasis.